Prevalence of conscientious objection to termination of pregnancy among health professionals in the Capricorn District of the Limpopo Province - Mohale, Tshepo Kabelo (My University, 2023)
Introduction: Women in South Africa have access to abortion services on demand thanks to the Choice on Termination of Pregnancy Act (CTOPA) 92 of 1996. The right to conscientious objection is one of the principal barriers to exercising this human right, which is protected by the constitution. In sub-Saharan African countries, there are little and questionable data on the prevalence of conscientious objection. Therefore, this study aimed to determine the prevalence of conscientious objections to the termination of pregnancy among healthcare professionals in the Capricorn District of Limpopo Province to ascertain the frequency of ethical objections to pregnancy termination among healthcare workers. Methodology: A quantitative, descriptive cross-sectional research design was used to collect data from healthcare professionals at the healthcare facilities of the Capricorn District of Limpopo Province. The researcher used statistical software for Windows, such as Statistical Data Analysis version 15 (STATA, corporation, USA), and a p-value of less than 0.05 will be considered statistically significant. Results: The overall prevalence of conscientious objection to termination of pregnancy was 55.4%. Conscientious objection to abortion was more common overall among both males and females as they aged. The healthcare professionals in the current study received were trained in a variety of methods to terminate a pregnancy, including manual vacuum aspiration, medical abortion, and dilatation and curettage. This study highlights the increasing rate of conscientious objection in the healthcare sector. Discussion: The current study revealed that conscientious objection to termination of pregnancy is not unique to Capricorn District of Limpopo Province in South Africa. The current study found that conscientious objection to abortion was common. Contrary to other studies, religion was found not to be significantly associated with a conscientious objection to termination of pregnancy in the current study.
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: Prevalence; Conscientious objection; Healthcare facility; Termination of pregnancy; Healthcare Professional; Maternal death; Abortion; Medical personnel; Conscientious objection